PEM fuel cell and supercapacitor hybrid power system for four in-wheel switched reluctance motors drive EV using geographic information system - Oksuztepe, Eyyup; Yildirim, Merve (Pergamon-Elsevier Science Ltd, 2024)
In recent years, Electric Vehicles (EVs) powered by a Proton Exchange Membrane Fuel Cell (PEMFC) which has high energy density and efficiency have become an attractive solution for the automotive industry. However, since the power density of the PEMFC is not high enough for different road conditions such as accelerating and going uphill, a supercapacitor (SC) is preferred as the auxiliary energy source for high power density in EVs. Thus, in this paper, a hybrid power system consisting of the Fuel Cell (FC) and SC for a Four-Wheel Drive Electric Vehicle (4WDEV) is proposed. Since energy requirement of the EV depends on the travel route, an effective Energy Management System can be designed by using a Geographic Information System (GIS). According to the road trajectory, the power requirement of the EV is estimated and thus, energy consumption is reduced. The proposed system is validated by using the Matlab Simscape Toolbox.
Keywords: Electric vehicle; Energy management system; Supercapacitor; PEM fuel cell; Geographic information system